Investment Casting of Microwave Components for E-Band - Panusch, David; Birkenhauer, Christoph; Gold, Gerald (European Microwave Week 2024, 2024)
The investment casting process was newly proposed for the production of microwave components, combining the advantages of additive manufacturing’s spatial freedom with an all-metal structure that was previously unavailable for the E-Band. This paper focuses on the effects of the manufacturing process of these components on casting quality and resulting electrical properties, which can be up to 2 dB better with adopting suitable design for manufacturing methods. The effective conductivity of different casting specific alloys is analyzed utilizing a resonator measurement, whereby an improvement of 20% from fine silver to an aluminium alloy could be determined. The results are compared to a conventional milled waveguide as a reference. Additionally, the waveguides slotted sidewalls are examined in a crosstalk stud
Keywords: 3D-printing; Additive Manufacturing; Conductivity Measurement; Slotted Waveguide; E-Band; lost wax casting; surface roughness; effective conductivity